Dinamika Dan Kemandirian Kelompok Badan Keswadayaan Masyarakat (BKM) Program Kota Tanpa Kumuh (KOTAKU) Di Kota Padang - M. Bajang Ahmadi; Fuad Madarisa; Asmawi (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2023)
Development based on groups becomes a participatory development approach pattern by involving the community directly through groups. This research aims: (1)To find out and analyze the characteristics of the members of BKM, National Slum Upgrading Program ( Program Kotaku ) in Padang city, (2)To find out and analyze the level of dynamics and independence of the BKM, National Slum Upgrading Program / Program Kotaku in Padang city and (3)To find out and analyze how much influence the characteristics of members and the level of dynamics on the independence of the BKM group in the KOTAKU Program in Padang City. This research was conducted using a quantitative approach. The data collection technique was carried out by distributing questionnaires offline to the BKM members in Padang City. Data management using SPSS version 24 by linear regretion analysis. The results of the study prove the majority of BKM members in the city of Padang are women aged between 46-65 years with an average education level of high school, the characteristics partially have no effect on the independence of the BKM group, the dynamics of the BKM group partially have a significant influence on the independence of the BKM. Both of characteristics and group dynamics have a positive and significant influence on the independence of the BKM group. The results also confirm that the level of group dynamics and group independence in Padang City is in the medium category, therefore strategic efforts need to be improved. The suggestions are: 1. Efforts are needed to increase the dynamics of the BKM group in Padang City, 2. In the future, it is hoped that young/productive generations will emerge to join BKM members to be more productive and more dynamic, because the more dynamic a group is, the more independent the group will be. This research is expected to provide input for the BKM group as well as for community empowerment program stakeholders, especially the KOTAKU Program, Directorate General of Human Settlements, Ministry of PUPR.